Effective triage in the Pacific region: The development and implementation of the Solomon Islands Triage Scale. (13th March 2019) - Wanefalea, Lynne E; Mitchell, Rob; Sale, Trina; Sanau, Elizabeth; Phillips, Georgina A
Abstract: Objective: The ED at the National Referral Hospital in Honiara, Solomon Islands, receives approximately 50 000 patients per year. A 2014 review of ED functioning identified deficiencies in triage processes. Placement of Australian volunteer advisors provided an opportunity to develop and implement a purpose‐designed triage system. Methods: Action research methodology and the 'plan, act, observe, reflect' cycle was employed, leading to the development of a three‐tier triage system based on the South African Triage Scale. ED patient flow and data management processes were simultaneously updated, and staff were trained in the new system. After a pilot period, the Solomon Islands Triage Scale was implemented in August 2017. Evaluation after 3 months of operation included predictive validity (using admission and case fatality rates as surrogate markers of urgency) and reliability (based on inter‐rater agreement at retrospective chart review by an independent nurse). Results: In the period 1 August to 31 October, there were 10 905 presentations, of which 97.1% were allocated a triage category (1% category 1, 21.3% category 2 and the remainder category 3). Admission rates correlated closely with triage category ( P < 0.01). The case fatality rate was 22.1% for category 1 patients, 0.09% for category 2 and 0.01% for category 3 ( P < 0.01). An audit of 96 records conducted in October 2017 revealed 88.4% agreement for triage category allocation. Conclusion: Solomon Islands Triage Scale is the first three‐tier triage scale to be implemented in the Pacific region and appears to have adequate validity and reliability. The partnership between Australian volunteers and local clinicians is a positive example of capacity development and represents a model that could be implemented in other resource‐limited settings.